Analisis Kualitas Pelayanan Askes di Rumah Sakit Umum Daerah Kabupaten Kudus - Saputri, Febrilia Laita; Larasati, Endang; Lestari, Hesti (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Service is basically a given activity to assist, prepare and take care of, whether it be goods or services of one party to the other party. Public services are said to be satisfactory if the quality or the service can meet the needs and expectations of the community served. If people are not satisfied with the services provided, the service quality is certainly not qualified or not efficient. To be able to assess the extent to which the quality of public services provided, there needs to be criteria that indicate whether a given public service can be said to be qualified or not. There are five dimensions as a measure of quality of service according to Zeithaml,dkk. This research aims to analyze the quality of Askes service in General Hospital of Kudus Region and people's expectations about health care in this hospital. The locus of this study is the General Hospital of Kudus Region in outpatient and inpatient Askes. This research uses descriptive qualitative research method with 7 (seven) informant. Informants selected a patient or user Askes BPJS ex. Askes. The results of this research are quality of Askes service in the General Hospital of Kudus Region has not qualified because there are still many lacks. The health service is still not up to the expectations of society because there are a lot of complaints and expectations expressed by informants. Required periodic evaluation of health services provided so that the government knows what it lacks and what needs to be repaired.